Post-Materialist Integral Ecology - Apffel-Marglin, Frédérique (Worldviews, 2018)
This essay is an example of a post-materialist science in the work of molecular biologist Candace Pert. Post-materialist science supersedes materialist-reductionist science and integrates spirituality with materiality. This discussion is motivated by the author’s experience as an academic in a New England institution. Integral ecology is entangled with post-material science as in the work of cosmologist Brian Swimme, Thomas Berry and Mary-Evelyn Tucker. The last part discusses the author’s creation of a non-profit organization in the Peruvian Upper Amazon. The work of her center is a response to requests by the local indigenous leadership for an alternative to their slash and burn form of agriculture. The alternative is the regeneration of a pre-Columbian anthropogenic Amazonian soil known as Terra Preta do Indio (black earth of the Indians) in Brazil, which integrates materiality and spirituality and offers the possibility of food security and sovereignty as well as climate mitigation.